piRNAs may regulate expression of candidate genes of esophageal adenocarcinoma - Akimniyazova, A. N.; Niyazova, T. K.; Yurikova, O. Yu.; Pyrkova, A. Yu.; Zhanuzakov, M. A.; Ivashchenko, A. T. (Frontiers in Genetics, 2022)
Elucidation of ways to regulate the expression of candidate cancer genes will contribute to the development of methods for cancer diagnosis and therapy. The aim of the present study was to show the role of piRNAs as efficient regulators of mRNA translation of esophageal adenocarcinoma (EAC) candidate genes. We used bioinformatic methods to study the interaction characteristics of up to 200 thousand piRNAs with mRNAs of 38 candidate EAC genes. The piRNAs capable of binding to mRNA of AR, BTG3, CD55, ERBB3, FKBP5, FOXP1, LEP, SEPP1, SMAD4, TP53 genes with high free energy by the formation of hydrogen bonds between canonical (G-C, A-U) and noncanonical (G-U, A-C) piRNA and mRNA nucleotide pairs were revealed. The organization of piRNA binding sites (BSs) in the mRNA of candidate genes was found to overlap nucleotide sequences to form clusters. Clusters of piRNA BSs were detected in the 5′-untranslated region, coding domain sequence, and 3′-untranslated region of mRNA. Due to the formation of piRNA binding site clusters, compaction of BSs occurs and competition between piRNAs for binding to mRNA of candidate EAC genes occurs. Associations of piRNA and candidate genes were selected for use as markers for the diagnosis of EAC.